2001
DOI: 10.1002/jmv.1019
|View full text |Cite
|
Sign up to set email alerts
|

Differential IgM response to conformational and linear epitopes of parvovirus B19 VP1 and VP2 structural proteins

Abstract: The IgM immune response against conformational and linear epitopes of B19 structural proteins VP1 and VP2 was examined in serum samples with a suspect B19 infection to determine the most suitable antigen for use in IgM detection and also to evaluate a possible relationship between the course of B19 infection and the presence of epitope type-specific IgM. The detection of IgM against conformational epitopes was performed by ELISA using undenatured VP1 and VP2 antigens whereas the detection of IgM against linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…It was previously reported that the antigenicity of the capsids containing VP1-2 proteins is different from that of the VP2-only capsids (28). Similarly, there were reports indicating that some samples might react with VP2-only capsids but not with VP2 capsids containing VP1 and vice versa (19)(20)(21). Although there might be differences in the antigenicity of VP1-2 and VP2-only capsids, they might be minor and not lead to significant changes in the overall reactivity of the antibody pool comprised of antibodies to multiple epitopes present in the capsid proteins.…”
Section: Discussionmentioning
confidence: 97%
“…It was previously reported that the antigenicity of the capsids containing VP1-2 proteins is different from that of the VP2-only capsids (28). Similarly, there were reports indicating that some samples might react with VP2-only capsids but not with VP2 capsids containing VP1 and vice versa (19)(20)(21). Although there might be differences in the antigenicity of VP1-2 and VP2-only capsids, they might be minor and not lead to significant changes in the overall reactivity of the antibody pool comprised of antibodies to multiple epitopes present in the capsid proteins.…”
Section: Discussionmentioning
confidence: 97%
“…Several VP2 and VP1u regions containing neutralizing epitopes have been identified (10, 32, 43). However, neutralizing linear epitopes seem to cluster in the N terminus of VP1u and the VP1-VP2 junction regions and to elicit a more efficient response than the epitopes in the VP2 region, which are mainly conformational epitopes (21,26,28,31,36). The inability to develop an efficient neutralizing immune response, as observed mainly in immunosuppressed individuals but also in otherwise healthy individuals, may result in the failure to eliminate the virus, thus leading to persistent infection and the possible occurrence of chronic diseases, such as chronic anemia or arthropathies (14).…”
mentioning
confidence: 99%
“…Circulating antibodies recognize both linear and conformational epitopes of the capsid proteins. Numerous investigators have demonstrated that B19V-specific IgG antibodies recognizing linear epitopes disappear around 6 months after infection, leaving only circulating antibodies that recognize conformational epitopes (4,7,15,17,20). Therefore, the nature of the viral antigen(s) used in the B19V-specific serologic assay is an important variable to consider in evaluating analytical test performance.…”
mentioning
confidence: 99%